Research on differential game model of vertical cooperation of dual-channel low-carbon supply chain - Wu, Mei-xiang; Shi, Cheng-dong; Sun, Qiang (International Journal of English Literature and Social Sciences (IJELS), 2020)
Direct channels for manufacturers have become the norm. For the study of double sales channels, single manufacturer, reducing emissions and single retailer promotion coordination problems, to emissions reductions as state variables, assume that the market demand by reduction, as well as the influence and promotion efforts to build a single manufacturer and single retailer of three kinds of differential game model, to investigate the condition of double channels involved in cooperation and the influence of various parameters on the members of the decision. It is found that under certain conditions, cost-sharing contracts can improve the profits of each member and the system. With the increase of the ratio of manufacturer to retailer's promotion cost, the improvement effect of the contract on the profit of the two members changed significantly. High retailers' low carbon advertising cost and discount rate factor will reduce the improvement effect of cost-sharing contract.